Recreational Physical Activity and Risk of Incident Knee Osteoarthritis: An International Meta‐Analysis of Individual Participant–Level Data. Issue 4 (10th March 2022) - Gates, Lucy S.; Perry, Thomas A.; Golightly, Yvonne M.; Nelson, Amanda E.; Callahan, Leigh F.; Felson, David; Nevitt, Michael; Jones, Graeme; Cooper, Cyrus; Batt, Mark E.; Sanchez‐Santos, Maria T.; Arden, Nigel K.
Abstract : Objective: The effect of physical activity on the risk of developing knee osteoarthritis (OA) is unclear. We undertook this study to examine the relationship between recreational physical activity and incident knee OA outcomes using comparable physical activity and OA definitions. Methods: Data were acquired from 6 global, community‐based cohorts of participants with and those without knee OA. Eligible participants had no evidence of knee OA or rheumatoid arthritis at baseline. Participants were followed up for 5–12 years for incident outcomes including the following: 1) radiographic knee OA (Kellgren‐Lawrence [K/L] grade ≥2), 2) painful radiographic knee OA (radiographic OA with knee pain), and 3) OA‐related knee pain. Self‐reported recreational physical activity included sports and walking/cycling activities and was quantified at baseline as metabolic equivalents of task (METs) in days per week. Risk ratios (RRs) were calculated and pooled using individual participant data meta‐analysis. Secondary analysis assessed the association between physical activity, defined as time (hours per week) spent in recreational physical activity and incident knee OA outcomes. Results: Based on a total of 5, 065 participants, pooled RR estimates for the association of MET days per week with painful radiographic OA (RR 1.02 [95% confidence interval (95% CI) 0.93–1.12]), radiographic OA (RR 1.00 [95% CI 0.94–1.07]), and OA‐related knee pain (RR 1.00 [95% CI 0.96–1.04]) were not significant. Similarly, the analysis of hours per week spent in physical activity also showed no significant associations with all outcomes. Conclusion: Our findings suggest that whole‐body, physiologic energy expenditure during recreational activities and time spent in physical activity were not associated with incident knee OA outcomes.